Report on an invasive pest, the fall armyworm Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) on maize cultivation in Bintulu, Sarawak - Muhamad Azmi Mohammed; Ameyra Aman-Zuki; Wan Asrina Wan Yahaya (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
The citation “Kalleshwaraswamy et al. (2018)” and “Kalleshwaraswamy, C.M., Maruthi, M.S. & Pavithra, H.B. 2018. Biology of invasive fall army worm Spodoptera frugiperda (JE Smith) (Lepidoptera: Noctuidae) on maize. Indian Journal of Entomology 80(3): 540-543.” in this entire manuscript have to be deleted and replace by “Sharanabasappa et al. (2018)” and “Sharanabasappa, D., Kalleshwaraswamy, C.M., Maruthi, M.S. & Pavithra, H.B. 2018. Biology of invasive fall army worm Spodoptera frugiperda (JE Smith) (Lepidoptera: Noctuidae) on maize. Indian Journal of Entomology 80(3): 540-543.”.The authors would like to relay our thanks and apologies to Dr. Sharanabassappa S. Deshmukh from the University of Agricultural and Horticultural Sciences, Shivamogga, Karnataka for the inconvenience caused.